Transforming neonatal care: a position paper on the potential of augmented and mixed reality - Rodrigues, Patrik Goncalves; Leandro, Danieli Mayumi Kimura; de Azevedo, Silvia Schoenau; Mimica, Marcelo Jenné; Rodrigues, Rafaela Fabri; Magalhães, Mauricio; dos Anjos, Bruno Fernandes; Variane, Gabriel Fernando Todeschi (Frontiers in Digital Health, 2025)
Mixed reality (MR) and augmented reality (AR) technologies bridge elements of the real and virtual worlds, emerging as tools that allow users to engage with digital cues to aid with tasks encountered in the physical environment. Thus, these holographic-based innovations are potential tools to support real-time patient care. The applications of MR and AR in neonatal care remain significantly underexplored. In the present article, we highlight the applications of MR and AR across medical procedures, physical examinations, medical diagnoses, and telemedicine, further underscoring their transformative potential within neonatal care. The use of MR and AR can be relevant across diverse economic and clinical landscapes, and in-depth research is required to evaluate the advantages of these tools in caring for neonates.